2015
DOI: 10.1097/ccm.0000000000001195
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tracheostomy Timing on Clinical Outcome and Adverse Events in Poor-Grade Subarachnoid Hemorrhage*

Abstract: Tracheostomy within 7 days of critical care admission is a feasible and safe procedure for patients with poor-grade subarachnoid hemorrhage. Early tracheostomy was not associated with an improvement in mortality or neurologic outcome but associated with fewer respiratory adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Tracheostomy is usually performed in critically ill patients who require prolonged mechanical ventilation. Tracheostomy has several established advantages over translaryngeal intubation, including reduced airway dead space and thus reduced work of breathing, facilitated weaning from mechanical ventilation, reduced undesired consequences of prolonged mechanical ventilation (e.g., ventilator-associated pneumonia and tracheal stenosis), convenient suctioning, and better patient comfort [3,4]. However, tracheostomy is not risk-free, and the optimal timing to perform tracheostomy remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Tracheostomy is usually performed in critically ill patients who require prolonged mechanical ventilation. Tracheostomy has several established advantages over translaryngeal intubation, including reduced airway dead space and thus reduced work of breathing, facilitated weaning from mechanical ventilation, reduced undesired consequences of prolonged mechanical ventilation (e.g., ventilator-associated pneumonia and tracheal stenosis), convenient suctioning, and better patient comfort [3,4]. However, tracheostomy is not risk-free, and the optimal timing to perform tracheostomy remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…also showed tracheostomy within 7 days of critical care admission for patients with poor-grade subarachnoid hemorrhage was associated with fewer respiratory adverse events. [ 14 ] However, ET had no impact on in-hospital mortality. [ 9 11 12 ] It has been suggested that ET should be recommended in traumatic brain injury patients who have a chance of survival.…”
Section: Introductionmentioning
confidence: 99%
“…Several mostly retrospective data previously published favor early surgical treatment. However, the literature on the optimal treatment of SEA displays various limitations: next to the retrospective nature of most publication, another limitation lies within the lack of a consensus of “early” and “late” procedures, as observed in other neurosurgical diseases [ 13 ]. Connor et al [ 3 ] reported their series consisting of 77 patients using a 3-day cutoff.…”
Section: Discussionmentioning
confidence: 99%